The lens parallax method: determining redshifts of faint blue galaxies through gravitational lensing - Bartelmann, Matthias; Narayan, Ramesh (Arxiv, 1995)
We propose a new technique, which we call the lens parallax method, to determine simultaneously the redshift distribution of the faint blue galaxies and the mass distributions of foreground clusters of galaxies. The method is based on gravitational lensing and makes use of the following: (1) the amplitude of lensing-induced distortions of background galaxies increases with redshift; (2) the surface brightnesses of galaxies decrease steeply with redshift. The distortions of galaxy images due to lensing are thus expected to be inversely correlated with surface brightness, allowing us to obtain relative distances to galaxies as a function of surface brightness. If the redshifts of the brightest galaxies are measured, then the relative distance scale can be converted to mean galaxy redshifts as a function of surface brightness. Further, by comparing the angular sizes of lensed galaxies with those of similar galaxies in empty control fields, it is possible to break the so-called mass sheet degeneracy inherent to cluster mass reconstruction techniques which are based purely on image ellipticities. This allows an unambiguous determination of the surface density of a lensing cluster. We describe an iterative algorithm based on these ideas and present numerical simulations which show that the proposed techniques are feasible with a sample of ~ 10 rich clusters at moderate redshifts ~ 0.3-0.4 and an equal number of control fields. The numerical tests show that the method can be used to determine the redshifts of galaxies with an accuracy of dz ~ 0.1-0.2 at z ~ 1-1.7, and to measure the masses of lensing clusters to about 5% accuracy.